The Influence of Social Media And E-Recruitment on Job Application Interest with Company Reputation as a Mediating Variable (Case Study on Students of the Faculty of Economics and Business, Universitas Muhammadiyah Surakarta) - Nadia Prasista Arisanti; Ahmad Mardalis (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study is to determine the effect of social media and e-recruitment on job application interest with company reputation as a mediating variable among students of the Faculty of Economics and Business, Muhammadiyah University Surakarta. This study was conducted using a quantitative approach. Data collection was carried out through a Likert scale-based questionnaire. The sampling method used in this study was nonprobability sampling, namely purposive sampling, where respondents were selected based on predetermined criteria, namely students of the Faculty of Economics and Business who were active on social media. From the data collection, a sample of 375 respondents was obtained. Furthermore, validity, reliability, and hypothesis testing were conducted using SmartPLS 3.0 software. The results obtained after the analysis process were that social media has a positive and significant effect on company reputation, e-recruitment has a positive and significant effect on company reputation, social media has a positive and significant effect on job applications, e-recruitment has a positive and significant effect on interest in applying for jobs, and company reputation has a positive and significant effect on interest in applying for jobs. Furthermore, company reputation was able to mediate the influence of social media on job application interest, and company reputation was able to mediate the influence of e-recruitment on job application interest.